Basic Documents in International Law, 4th. ed. - Hamid, Abdul Ghafur@Khin Maung Sein (Harun M. Hashim Law Centre, Ahmad Ibrahim Kulliyyah of Laws, 2012)
The purpose of this book is to provide the students of international law with a convenient collection of the texts that are essential to the study of the subject. The basic documents have been carefully selected and edited in order that they are in conformity with the course outlines of Public International Law I (LAW 3910) and Public International Law II (LAW 3911). In this Fourth edition, the book has been thoroughly revised and updated with recent conventions and Malaysian statutes.